Fish viruses and bacteria : pathobiology and protection - Cipriano, Rocco C., Ed. Woo, Patrick T. K., Ed (CABI, 2017)
This book contains 25 illustrated chapters that describe the epidemiology, prevalence, distribution, transmission, physiopathology, clinical signs, diagnosis, prevention, control strategies, legislative aspects and economic impact of bacterial and viral diseases of fishes, including: Infectious pancreatic necrosis virus; Infectious haematopoietic necrosis virus; Viral haemorrhagic septicaemia virus; Epizootic haematopoietic necrosis and European catfish virus; Oncorhynchus masou virus and Cyprinid herpesvirus; Infectious salmon anaemia virus; Spring viraemia of carp virus; Channel catfish viral Disease; Largemouth bass viral disease; Koi herpesvirus disease; viral encephalopathy and retinopathy; red sea bream iridovirus and white sturgeon iridovirus; alphaviruses; Aeromonas salmonicida and A. hydrophila; Edwardsiella spp.; Flavobacterium spp.; Francisella noatunensis; Mycobacterium spp.; Photobacterium damselae; Piscirickettsia salmonis; Renibacterium salmoninarum; Streptococcus iniae and S. agalactiae; Vibrio anguillarum, V. ordalii and Aliivibrio salmonicida; Weissella ceti and Yersinia ruckeri. This book is intended for research scientists in the aquaculture industry and universities, fish health consultants, managers and supervisors of fish health laboratories and veterinary specialists in commercial aquaria. It is also appropriate for the training of fish health specialists and for senior undergraduate/graduate and veterinary students who are conducting research on diseases of fish, as well as being a useful reference book for university courses on infectious diseases, general microbiology and the impacts of diseases on the aquaculture industry.